Current State of the Opioid Epidemic as it Pertains to Pediatric Orthopaedics From the Advocacy Committee of the Pediatric Orthopaedic Society of North America. Issue 5 (May 2018) - Raney, Ellen M.; van Bosse, Harold J.P.; Shea, Kevin G.; Abzug, Joshua M.; Schwend, Richard M.
Abstract : Introduction: The opioid epidemic in the United States has reached crisis proportions. Urgent response is needed. Hydrocodone in combination with acetaminophen is the most prescribed drug in the United States. The most common source of opioids available for misuse is the unused portions of postoperative prescriptions. Among high school seniors, 80% of those who reported nonmedical use of prescription opioids previously had legitimate prescriptions but recreationally used leftover doses. Roughly one-quarter of patients do not take any of their postoperatively prescribed opioids and the remainder take one-third to two-thirds of the prescribed doses. Methods: A summary of the literature is presented beginning from historical perspective to current status and pertinent strategies in dealing with this complicated problem. This review includes data from an electronic survey of the members of the Pediatric Orthopaedic Society of North America (POSNA) with regard to the prescriptions they would provide for 7 treatment scenarios. Results: Strategies for the preoperative, intraoperative, and postoperative phases of management of pain as well as strategies for education, research, and advocacy are presented. The Pediatric Orthopaedic Society of North America survey yielded 264 respondents. The 3 most commonly used opioid medications were hydrocodone, oxycodone, and acetaminophen with codeine, in that order, for most of the scenarios. The time period covered by postoperative prescriptions varied considerably. Conclusions: The magnitude of this problem is overwhelming. Education of care providers, patients and families, standardization of narcotic prescribing practices which incorporate patient characteristics, and appropriate plans for disposal of unused narcotics are immediate concepts to consider in correcting this problem. Long-term issues to tackle will be changing patient a family expectations, legislation, and obtaining additional resources directed towards this issue.